2012
DOI: 10.1007/s12182-012-0218-5
|View full text |Cite
|
Sign up to set email alerts
|

An experimental investigation on the effect of grain size on oil-well sand production

Abstract: Sand production in oil wells is closely related to the mechanical behavior and petrographical properties of sandstones reservoir. Grain size is one of the main parameters controlling the phenomenon, which is studied in this paper. Large-scale hollow cylindrical synthetic samples with the same rock strength but different grain sizes were tested by an experimental setup in the laboratory. Different external grain size (D 50 <0.3 mm), the required confining stress for different sanding levels decreased with an in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
16
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 42 publications
0
16
0
Order By: Relevance
“…He reported that the cavity enlargement decreases the sand initiation stress, whereas stronger samples show higher sand initiation stress. Similar parameters were studied by Fattahpour et al [2,3]. They recognized five distinct sand production stages in their experiments, including sand initiation, transient, semi-continuous, continuous, and catastrophic sand production.…”
Section: Introductionmentioning
confidence: 59%
See 2 more Smart Citations
“…He reported that the cavity enlargement decreases the sand initiation stress, whereas stronger samples show higher sand initiation stress. Similar parameters were studied by Fattahpour et al [2,3]. They recognized five distinct sand production stages in their experiments, including sand initiation, transient, semi-continuous, continuous, and catastrophic sand production.…”
Section: Introductionmentioning
confidence: 59%
“…It can be summarized as the separation and erosion of grain particles from the wellbore wall, along with the extraction of hydrocarbons. Redistribution of in-situ stress or the increased effective stress (in a depleting reservoir) leads to the failure of weak rock around the wellbore [2][3][4][5][6]. Consequently, some parts of the rock are disintegrated and may dislocate and enter the extraction well as a result of flowinduced hydrodynamic forces.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sand production is one of the common problems in oil and gas production wells drilled in unconsolidated formations (Fattahpour et al 2012). The abrasive flow of sand grains inside the wells and production lines leads to undesirable consequences including erosion of downhole or wellhead equipment, clogging of downhole equipment, subsidence of formation rock, walls destruction, reduction in reservoir recovery, maintenance cost, and in severe cases even death of the well (Ikporo and Sylvester 2015;Isehunwa and Olanrewaju 2010;Pedersen et al 2017;Singh and van Petegem 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Sand production has been a major obstacle for the successful exploitation of weakly consolidated /unconsolidated oil and gas reservoirs worldwide. It is reported that 70% of the global hydrocarbon reservoirs are susceptible to sand production (Fattahpour et al 2012). Typically, sand production is defined as sand particles in weakly consolidated subsea hydrocarbon-bearing sediments moving into the exploitation well along with the hydrocarbon and water flows, due to drilling and completion activities.…”
Section: Introductionmentioning
confidence: 99%